Comparative Law on Notary Dual Position between Indonesia and Germany - Nadia Maisa Alya; Rio Adrian (Repertorium: Jurnal Ilmiah Hukum Kenotariatan, 2026)
One of the important issues in notarial practice in Indonesia is the dual position of notaries, namely when a notary holds another profession that may potentially create conflicts of interest and disrupt their independence as a public official. Although the Notary Office Act (UUJN) explicitly prohibits dual positions, this practice still frequently occurs and raises problems that can affect the professionalism and integrity of notaries. In a comparative context, Germany has an interesting regulation through the Bundesnotarordnung (BNotO) which distinguishes two models of notary positions, namely Nur-Notar (pure notary) and Anwaltsnotar (lawyer simultaneously serving as notary). This study uses a normative juridical method with a comparative law approach to analyze the regulation and practice of prohibiting dual notary positions in Indonesia and Germany. The results show that both countries emphasize the independence and neutrality of notaries, yet Germany provides limited exceptions through the Anwaltsnotar model which is strictly regulated and supervised by notarial institutions at the state level. This system demonstrates a balance between the need for legal profession flexibility and protection of public interest. This comparison is expected to serve as a reference in strengthening the supervision system and professional ethics of notaries in Indonesia to be more professional, integrity-driven, and aligned with the principles of good governance in legal services. Keywords: Notary Dual Position; Indonesia; Germany